ПРЕИМУЩЕСТВА ПРИМЕНЕНИЯ ИРРИГАЦИОННЫХ ОТСТОЙНИКОВ МАГИСТРАЛЬНЫХ И МЕЖХОЗЯЙСТВЕННЫХ КАНАЛОВ КАРАКАЛПАКСТАНА - Байманов, К.И.; Тажибаев, Ш.Д.; Назарбеков, К.К. (SCIENCE and SOCIETY, 2024)
The article presents the results of many years in the field studies of siltation processes in irrigation systems in the lower reaches of the river. Amu Darya. Patterns of siltation and purification of suspended sediment have been identified, and conditions for improving the normal operation of irrigation canals have been shown.
Keywords: sediments; culvert; water intake; sedimentation tank; dredger; slurry pipelines; dumps; papillonization; construction